Designing a package of sexual and reproductive health and HIV outreach services to meet the heterogeneous preferences of young people in Malawi: Results from a discrete choice experiment - Christine Michaels-Igbokwe; Mylene Lagarde; John Cairns; Fern Terris-Prestholt (Health Economics Review, 2015)
Background: This article examines young people's preferences for integrated family planning (FP) and HIV services in rural Malawi. Different hypothetical configurations for outreach services are presented using a Discrete Choice Experiment (DCE). Responses are analysed using Random Parameters Logit and Generalised Mixed Logit (GMXL) models in preference space and a GMXL model parameterised in willingness-to-pay space. Simulations are used to estimate the proportion of respondents expected to choose different service packages as elements are varied individually and in combination. Results: Responses were collected from 537 young people aged 15-24. Results show that when considering attending an outreach service to access family planning young people value confidentiality and the availability of HIV services including HIV counselling and testing (HCT) and HIV treatment, though significant observable and unobservable heterogeneity is present. Female respondents and those aged 20-24 were less concerned with service confidentiality compared to male respondents and those aged 15-19; respondents who were in a relationship at the time of the survey valued confidentiality more than those who reported being single. The addition of sports and recreation for young people may also be an attractive feature of a youth-friendly service; however, preferences for this attribute vary according to respondent gender. Results of the simulation modelling indicate that the most preferred service package is one that offers confidential services, both HCT and HIV treatment and sports for youth, with up to 32% of respondents expected to choose this service over a service where clients may have concerns over confidentiality, only HCT is available and there are no additional activities for young people. Estimates of willingness-to-pay for service attributes indicate that respondents were willing to pay up to USD1.76 for confidentiality, USD0.65 for a service offering both HCT and HIV treatment and USD0.26 for a service including sports for youth. Conclusions: Young people were able to complete a complex DCE and appeared to trade between the different characteristics used to describe the outreach services. These findings may offer important insight to policy makers designing youth friendly SRH outreach services and providers aiming to improve the acceptability and uptake of FP services.
Keywords: 330; Discrete choice experiment; Young people; Sexual and Reproductive Health; Family planning; HIV; Outreach